P(3)-[2-(4-hydroxyphenyl)-2-oxo]ethyl ATP for the rapid activation of the Na(+),K(+)-ATPase. - Geibel, S (2000)
P(3)-[2-(4-hydroxyphenyl)-2-oxo]ethyl ATP (pHP-caged ATP) has been investigated for its application as a phototrigger for the rapid activation of electrogenic ion pumps. The yield of ATP after irradiation with a XeCl excimer laser (lambda = 308 nm) was determined at pH 6.0-7.5. For comparison, the photolytic yields of P(3)-[1-(2-nitrophenyl)]ethyl ATP (NPE-caged ATP) and P(3)-[1, 2-diphenyl-2-oxo]ethyl ATP (desyl-caged ATP) were also measured. It was shown that at lambda = 308 nm pHP-caged ATP is superior to the other caged ATP derivatives investigated in terms of yield of ATP after irradiation. Using time-resolved single-wavelength IR spectroscopy, we determined a lower limit of 10(6) s(-1) for the rate constant of release of ATP from pHP-caged ATP at pH 7.0. Like NPE-caged ATP, pHP-caged ATP and desyl-caged ATP bind to the Na(+), K(+)-ATPase and act as competitive inhibitors of ATPase function. Using pHP-caged ATP, we investigated the charge translocation kinetics of the Na(+),K(+)-ATPase at pH 6.2-7.4. The kinetic parameters obtained from the electrical measurements are compared to those obtained with a technique that does not require caged ATP, namely parallel stopped-flow experiments using the voltage-sensitive dye RH421. It is shown that the two techniques yield identical results, provided the inhibitory properties of the caged compound are taken into account. Our results demonstrate that under physiological (pH 7.0) and slightly basic (pH 7.5) or acidic (pH 6. 0) conditions, pHP-caged ATP is a rapid, effective, and biocompatible phototrigger for ATP-driven biological systems.